-25-3× { [49 ÷ (-7) -(-2)×(8-7×3)] × (-2)^3 + (-68) ÷(-2)^3}
Răspunsuri la întrebare
Răspuns de
0
-25-3× { [49 ÷ (-7) -(-2)×(8-7×3)] × (-2)^3 + (-68) ÷(-2)^3} =
-25-3× { [(-7) -(-2)×(8-21)] × (-8) + (-68) ÷(-8)} =
-25-3× { [(-7) -(-2)×(-13)] × (-8) + (-68) ÷(-8)} =
-25-3× [(-7 - 26) × (-8) + (-68) ÷(-8)] =
-25-3× [(-33) × (-8) + (-68) ÷(-8)] =
-25-3× (264+ 17/2) =
-25-3× [(528+ 17)/2] =
-25-3× (545/2) = -25-1635/2 = -1685/2
-25-3× { [(-7) -(-2)×(8-21)] × (-8) + (-68) ÷(-8)} =
-25-3× { [(-7) -(-2)×(-13)] × (-8) + (-68) ÷(-8)} =
-25-3× [(-7 - 26) × (-8) + (-68) ÷(-8)] =
-25-3× [(-33) × (-8) + (-68) ÷(-8)] =
-25-3× (264+ 17/2) =
-25-3× [(528+ 17)/2] =
-25-3× (545/2) = -25-1635/2 = -1685/2
Alte întrebări interesante
Engleza,
8 ani în urmă
Istorie,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Geografie,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă